Evaluation of essential and heavy metal levels in pasteurized and long-life cow milk - Atiga Elbagermi, Mohamed; Abdulmajid Bin Haleem, Antisar; Muftah Elsherif, Khaled (International Journal of Advanced Chemistry, 2020)
In the present investigation, 11 cowâ€™s milk samples (pasteurized and long life) were collected from supermarkets in Misurata city, Libya. For the determination of metal contents, the milk samples were subjected to the optimized microwave digestion method using HNO3 and H2O2. The levels of Na, K, Mg, Ca, Fe, Cu, Cr, Mn, Co, Ni, Zn, Cd, and Pb were evaluated by Microwave Plasma - Atomic Emission Spectrophotometer (MP-AES 4100). It was found that potassium is the most concentrated essential metal while zinc is the highest detected heavy metal in all milk samples. The levels of Co and Cd were not detected in all milk samples under investigation (lower than instrumental detection limits). The mean concentrations of the detected metals were as follows: 828.05Â±0.82, 587.57Â±0.87, 512.38Â±0.30, 73.79Â±0.19, 2.014Â±0.19, 1.89Â±0.16, 0.178Â±0.03, 0.061Â±0.02, 0.074Â±0.01, 0.053Â±0.001, and 0.045Â±0.001 for: K, Ca, Na, Mg, Zn, Fe, Cu, Mn, Ni, Pb, and Cr ppm, respectively. There is no significant difference in the mean concentrations of Ni, Cr and Pb between the investigated milk samples. Though, the levels of essential and heavy metals observed were similar with other reported values in the literature.Â Â